Proteomic analysis identifies interleukin 11 regulated plasma membrane proteins in human endometrial epithelial cells in vitro - Stanton Peter G; Lee Ming Yee; Foo Caroline FH; Yap Joanne; Dimitriadis Evdokia (BMC, 2011)
Abstract Background During the peri-implantation period, the embryo adheres to an adequately prepared or receptive endometrial surface epithelium. Abnormal embryo adhesion to the endometrium results in embryo implantation failure and infertility. Endometrial epithelial cell plasma membrane proteins critical in regulating adhesion may potentially be infertility biomarkers or targets for treating infertility. Interleukin (IL) 11 regulates human endometrial epithelial cells (hEEC) adhesion. Its production is abnormal in women with infertility. The objective of the study was to identify IL11 regulated plasma membrane proteins in hEEC in vitro using a proteomic approach. Methods Using a 2D-differential in-gel electrophoresis (DIGE) electrophoresis combined with LCMS/MS mass spectrometry approach, we identified 20 unique plasma membrane proteins differentially regulated by IL11 in ECC-1 cells, a hEEC derived cell line. Two IL11 regulated proteins with known roles in cell adhesion, annexin A2 (ANXA2) and flotillin-1 (FLOT1), were validated by Western blot and immunocytochemistry in hEEC lines (ECC-1 and an additional cell line, Ishikawa) and primary hEEC. Flotilin-1 was further validated by immunohistochemistry in human endometrium throughout the menstrual cycle (n = 6-8/cycle). Results 2D-DIGE analysis identified 4 spots that were significantly different between control and IL11 treated group. Of these 4 spots, there were 20 proteins that were identified with LCMS/MS. Two proteins; ANXA2 and FLOT1 were chosen for further analyses and have found to be significantly up-regulated following IL11 treatment. Western blot analysis showed a 2-fold and a 2.5-fold increase of ANXA2 in hEEC membrane fraction of ECC-1 and Ishikawa cells respectively. Similarly, a 1.8-fold and a 2.3/2.4-fold increase was also observed for FLOT1 in hEEC membrane fraction of ECC-1 and Ishikawa cells respectively. In vitro, IL11 induced stronger ANXA2 expression on cell surface of primary hEEC and ECC-1 whilst, the lipid-raft protein FLOT1 demonstrated punctate staining in the apical surface of ECC-1 plasma membranes and was upregulated in the epithelium in the receptive phase of the menstrual cycle (p lower or equal 0.05). Conclusions This is the first study to use a proteomics approach to identify hEEC plasma membrane proteins that may be useful as infertility markers or pharmacological targets for fertility regulation.